(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
The control of convective heat transfer from a heated circular cylinder immersed in an electrically conducting fluid is achieved using an externally imposed magnetic field. A Higher Order Compact Scheme (HOCS) is used to solve the governing energy equation in cylindrical polar coordinates. The HOCS gives fourth order accurate results for the temperature field. The behavior of local Nusselt number, mean Nusselt number and temperature field due to variation in the aligned magnetic field is evaluated for the parameters 5≤Re≤40, 0≤N≤20 and 0.065≤Pr≤7. It is found that the convective heat transfer is suppressed by increasing the strength of the imposed magnetic field until a critical value of N, the interaction parameter, beyond which the heat transfer increases with further increase in N. The results are found to be in good agreement with recent experimental studies.